2018
DOI: 10.1186/s12885-018-4554-8
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 assessment in pediatric rhabdomyosarcoma: a pilot study

Abstract: BackgroundRhabdomyosarcomas (RMSs) are the most frequent soft tissue sarcoma in children and adolescents, defined by skeletal muscle differentiation and the status of FOXO1 fusions. In pediatric malignancies, in particular RMS, scant and controversial observations are reported about PD-L1 expression as a putative biomarker and few immune checkpoint clinical trials are conducted.MethodsPD-L1 assessment was evaluated by immunohistochemistry (IHC) utilizing two anti-PDL1 antibodies, in a pilot cohort of 25 RMS. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
(30 reference statements)
3
10
0
2
Order By: Relevance
“…In sarcomas, despite pre-clinical studies suggesting a potential role for checkpoint inhibitor therapy, early clinical trials using pembrolizumab or nivolumab as single agents have shown very limited efficacy 44 , 45 . There are no reports of pediatric sarcoma with CR to anti-PD-1 therapy alone, and pre-clinical studies on expression of PD-L1 in pediatric RMS are limited 46 . In view of the upregulation of PD-1 on CD8+ CAR+ T cells following repeat infusions during CR1, we reasoned that incorporating pembrolizumab with CAR T cells could improve CAR T-cell function and lead to clinical benefit in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…In sarcomas, despite pre-clinical studies suggesting a potential role for checkpoint inhibitor therapy, early clinical trials using pembrolizumab or nivolumab as single agents have shown very limited efficacy 44 , 45 . There are no reports of pediatric sarcoma with CR to anti-PD-1 therapy alone, and pre-clinical studies on expression of PD-L1 in pediatric RMS are limited 46 . In view of the upregulation of PD-1 on CD8+ CAR+ T cells following repeat infusions during CR1, we reasoned that incorporating pembrolizumab with CAR T cells could improve CAR T-cell function and lead to clinical benefit in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…All antibodies were incubated with a commercially available detection kit (EnVision™ FLEX+, Dako, Denmark) in an automated Immunostainer (Dako Autostainer System—Link 48). The status of PD-L1 protein expression was also investigated utilizing clone anti PD-L1 22C3 (Dako, Glostrup, Denmark), as previously described [47].…”
Section: Methodsmentioning
confidence: 99%
“…In OS, PD-L1 expression correlates with immune cell infiltration, including NK cells, T cells, and dendritic cells, as well as significantly poorer 5-year event free survival [17]. Although PD-L1 blockade has shown effect in various cancers, Majzner et al recently characterized the frequency of PD-L1 expression in several sarcomas and reported only minimal expression on tumor cells of OS, EWS, and RMS samples [23, 24]. Despite these data, PD-L1 expression on tumor cells may not be necessary for immunotherapeutic effect from immune checkpoint blockade (ICB) [25]; moreover, the role of microRNA may be equally important [26].…”
Section: Checkpoint Inhibitorsmentioning
confidence: 99%